2006
DOI: 10.1152/ajpheart.00543.2005
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin gene-related peptide activates different signaling pathways in mesenteric lymphatics of guinea pigs

Abstract: The effects of calcitonin generelated peptide (CGRP) on constriction frequency, smooth muscle membrane potential (V m), and endothelial Vm of guinea pig mesenteric lymphatics were examined in vitro. CGRP (1-100 nM) caused an endothelium-dependent decrease in the constriction frequency of perfused lymphatic vessels. The endothelium-dependent CGRP response was abolished by the CGRP-1 receptor antagonist CGRP-(8 -37) (1 M) and pertussis toxin (100 ng/ml). This action of CGRP was also blocked by the nitric oxide (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
30
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 52 publications
3
30
0
Order By: Relevance
“…Thus activation/deactivation of K ATP located on the plasma membrane signifi cantly contributed to the regulation of lymphatic activity [8][9][10][11][12][13]. In the present study, the vessels were pressurized for the production of spontaneous activity of smooth muscles in the thoracic ducts, as well as previous studies [9][10][11][12].…”
Section: Involvement Of K Atp and Casupporting
confidence: 53%
See 1 more Smart Citation
“…Thus activation/deactivation of K ATP located on the plasma membrane signifi cantly contributed to the regulation of lymphatic activity [8][9][10][11][12][13]. In the present study, the vessels were pressurized for the production of spontaneous activity of smooth muscles in the thoracic ducts, as well as previous studies [9][10][11][12].…”
Section: Involvement Of K Atp and Casupporting
confidence: 53%
“…The presence of mitochondria and glycogen granules seems to produce ATP in the lymphatic smooth muscles with spontaneous activity. These morphological fi ndings may be associated with fi ndings that lymphatic smooth muscle cells have ATP-sensitive K + channels (K ATP ), which contribute to the regulation of functions including the formation of membrane potentials, maintenance of myogenic tone, and contractility and/or frequency of lymph pump activity [8][9][10][11][12][13]. We have shown that the mechanical activities of lymphatic smooth muscles are governed by metabolic dependent regulatory mechanisms, such as the intracellular concentration of ATP.…”
mentioning
confidence: 87%
“…First, it is well known that sympathetic sprouting is important for infarct healing and scar formation, especially in angiogenesis and lymphangiogenesis (3,4,20), whereas the murine HTx preparation is devoid of innervation and lacks communication with cervical ganglions and the central nervous system. Therefore, its potential impact on the inflammatory response and on cardiac neural stem cell function (10) during LV unloading cannot be clarified in the present work.…”
Section: Discussionmentioning
confidence: 99%
“…This combination of smooth and striated muscle contractile elements present in lymphatic muscle could provide unique contractile characteristics (i.e., Ca 2ϩ sensitivity and cooperativity) for lymphatic myofilaments. Although numerous mechanical (3,12,30,35,49) and neurohumoral (1,2,19,31,46,50) factors have been shown to modulate the tonic and phasic activity of collecting lymphatics, few investigations of the basic contractile properties of the lymphatic myofilament have been published.…”
mentioning
confidence: 99%